THE EFFECTIVENESS OF GROUP COUNSELING SERVICES WITH PSYCHODRAMA TECHNIQUES REDUCING THE ACADEMIC PROCRASTINATION BEHAVIOR OF STUDENTS OF SMA NEGERI 1 LINTAU - Hariyati Ati; Silvianetri Silvianetri; Ardimen Ardimen; Yuliana Nelisma (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2021)
Abstract The background of this research is that most of the students at SMA Negeri 1 Lintau postpone their academic assignments even though the counselor has made many efforts in counseling, but the results are not significant. Therefore, a new technique is needed to overcome this problem. This study aims to investigate the effectiveness of group counseling services with psychodrama techniques to reduce academic procrastination of students at SMA Negeri 1 Lintau in academics. The design of this study was a quasi-experimental with one group pretest and posttest design. The population in this study were students of class XI SMA N 1 Lintau in the 2020/2021 academic year. Samples were selected by simple random sampling. The sample is class XI IPS 4. Then, 20 students are devided into 2. groups; 10 students as the experimental class and 10 students as the control class. The instrument used to obtain the data is a procrastination questionnaire. Independent sample T-test and N-Gain analysis were used to analyze the data. The results of the study showed that students' academic procrastination decreased after applying psychodrama techniques, but this approach was not effective in reducing students' academic procrastination significantly based on the N-Gain analysis. In conclusion, psychodrama techniques are effective in reducing students' academic delays. The results showed that students' academic procrastination was reduced after applying the psychodrama approach, but this approach was not effective in reducing students' academic procrastination significantly based on the N-benefit analysis. In conclusion, psychodrama techniques are effective in reducing academic procrastination. The results showed that students' academic procrastination decreased after applying psychodrama techniques, but this approach was not effective in reducing students' academic procrastination significantly based on the N-Gain analysis. In conclusion, psychodrama techniques are effective in reducing students' academic procrastination. Keywords: Group Counseling Services, Psychodrama Techniques, Academic Procrastination Behavior AbstractPenelitian ini dilatarbelakangi bahwa sebagian besar siswa di SMA Negeri 1 Lintau menunda tugas akademiknya meskipun konselor telah melakukan berbagai upaya dalam konseling tetapi hasilnya tidak signifikan. Oleh karena itu, diperlukan teknik baru untuk mengatasi masalah tersebut. Penelitian ini bertujuan untuk mengetahui efektivitas layanan konseling kelompok dengan teknik psychodrama untuk mengurangi prokrastinasi akademik siswa SMA Negeri 1 Lintau di bidang akademik. Desain penelitian ini adalah eksperimen semu dengan one group pretest and posttest design. Populasi dalam penelitian ini adalah siswa kelas XI SMA N 1 Lintau tahun pelajaran 2020/2021. Sampel dipilih secara simple random sampling. Sampelnya adalah kelas XI IPS 4. Kemudian, 20 siswa dibagi menjadi 2. kelompok; 10 siswa sebagai kelas eksperimen dan 10 siswa sebagai kelas kontrol. Instrumen yang digunakan untuk memperoleh data adalah angket penundaan. Uji-T sampel independen dan analisis N-Gain digunakan untuk menganalisis data. Hasil penelitian menunjukkan bahwa prokrastinasi akademik siswa menurun setelah menerapkan teknik psychodrama, namun pendekatan ini tidak efektif dalam mengurangi prokrastinasi akademik siswa secara signifikan berdasarkan analisis N-Gain. Kesimpulannya, teknik psikodharma efektif dalam mengurangi keterlambatan akademik siswa. Hasil penelitian menunjukkan bahwa prokrastinasi akademik siswa berkurang setelah menerapkan pendekatan psikodharma, namun pendekatan ini tidak efektif dalam mengurangi prokrastinasi akademik siswa secara signifikan berdasarkan analisis N-benefit. Kesimpulannya, teknik psychodrama efektif dalam mengurangi prokrastinasi akademik. Hasil penelitian menunjukkan bahwa prokrastinasi akademik siswa menurun setelah menerapkan teknik psychodrama, namun pendekatan ini tidak efektif dalam mengurangi prokrastinasi akademik siswa secara signifikan berdasarkan analisis N-Gain. Kesimpulannya, teknik psikodharma efektif dalam mengurangi prokrastinasi akademik siswa. Keywords: Group Counseling Services, Psychodrama Techniques, Academic Proctination Behavior